Uso tradicional de plantas medicinales en gestantes del centro materno Perinatal de Tarapoto - Tapullima Rojas, Mirian (2001)
The present study was carried out in order to know the percentage of use of herbs during pregnancy and what are the factors associated with this. 258 surveys applied to pregnant women who attended the maternal Perinatal Center during 1998. Surveyed 198 referred to use herbs to relieve some discomfort of pregnancy after the analysis of the collected information was reached the following conclusions: 77% of pregnant women attending the maternal Perinatal center used medicinal plants in different diseases that suffer from pregnancy and 23' I do not make use of these. The plant most used during pregnancy is the Mallow (68.7 ' I) and secondly the puspino sheet (16.2%); the mother in a 73.2 ' I and 10% grandparents are transmitting the teachings. On the use therapeutic of the plants being more used in tea and table (plywood). More treated clinical forms are pelvic inflammation (46 5' I), follow...